Reproduction, infection and killer-cell immunoglobulin-like receptor haplotype evolution - Penman, B; Moffett, A; Chazara, O; Gupta, S; Parham, P (Springer Berlin Heidelberg, 2016)
Killer-cell immunoglobulin-like receptors (KIRs) are encoded by one of the most polymorphic families in the human genome. KIRs are expressed on natural killer (NK) cells, which have dual roles: (1) in fighting infection and (2) in reproduction, regulating hemochorial placentation. Uniquely among primates, human KIR genes are arranged into two haplotypic combinations: KIR A and KIR B. It has been proposed that KIR A is specialized to fight infection, whilst KIR B evolved to help ensure successful reproduction. Here we demonstrate that a combination of infectious disease selection and reproductive selection can drive the evolution of KIR B-like haplotypes from a KIR A-like founder haplotype. Continued selection to survive and to reproduce maintains a balance between KIR A and KIR B.